Estudo da absorção de óleo em revestimentos de produtos empanados - Lucas, Kelcilene Cristina (2011)
The importance of food service in the national economy grew at an average of 3% per annum over the past 10 years, which can be explained by the significant changes in the habits of the Brazilians, imposed by the modern world. There is a clear trend of increasing market demand for ready products for consumption, which is a result of changing population lifestyle. Many foods, before the frying process, are breaded with corn flour. This outer layer concentrates a higher oil absorption during the frying process. Some ingredients have been added to the coatings of breaded products to decrease the oil absorption. Among the different gums used as barriers to fat, the use of starch, which has the unique property of thermal gelation, was the target of this study. In this work, a method for treatment of corn flour was developed to reduce the oil absorption of steaks and nuggets, adding a solution of pregelatinized starch. The effect of the amount of gelatinized starch solution on the oil retention in fried corn flour was evaluated. Different amounts of a starch solution (30 %wt) were added to corn flour, keeping the humidity constant. The results showed that the addition of 3 g of gelatinized starch solution to 10 g of corn flour had the lowest oil absorption, with a reduction of about 21.5% in oil absorption when compared with the absorption of the sample without treatment. This condition contained enough solution to coat the flour particles, enhancing the formation of gelatinous film which acted as a resistance to entry of oil, promoting sealing the pores of the corn flour. Thus, this work contributes to the development of a less caloric fried product, enabling consumers to enjoy the unique flavor that the frying process provides to food. Furthermore, the implementation of starch-based coatings in the manufacturing process reduce the oil retention during the pre-frying, decreasing the amount of oil that should be returned to the process, and, consequently, process operational cost.